Penentu Profitabilitas Bank Syariah di Dunia: Likuiditas, Risiko Pembiayaan, dan Teknologi: Likuiditas, Risiko Pembiayaan, dan Teknologi - Violinda Syahgaria Firdaus; Guntur Kusuma Wardana (Shafin: Sharia Finance and Accounting Journal, 2026)
The development of Islamic banking worldwide has not been accompanied by evenly distributed profitability levels among banks across different regions. This condition indicates that internal factors within Islamic banks contribute to the differences in financial performance. This study examines profitability dynamics in Islamic banking by focusing on liquidity conditions, financing risk, and technological factors. The analysis draws on bank-level observations from 34 Islamic banks selected from 52 institutions affiliated with the Islamic Financial Services Board over the 2020–2024 period, forming a balanced panel dataset. Empirical panel data analysis indicates that liquidity indicators, including the FDR, Quick Ratio, and Cash Ratio, are closely associated with profitability. Financing risk also emerges as a significant factor, whereas technological factors do not show a statistically meaningful effect on profitability during the observed period. Considering all the findings as a whole, effective risk control procedures and appropriate liquidity strategies have a significant impact on the ability of Islamic banks to achieve long-term profitability globally.